Molecular detection ofHistoplasma capsulatumin bats of the Amazon biome in Para state, Brazil - Silva, Josileide Araujo da; Scofield, Alessandra; Barros, Flavia de Nazare; Farias, Diana Maria de; Riet-Correa, Gabriela; Bezerra Junior, Pedro Soares; Santos, Tiago Felipe Souza; Tavares, Gabriel Savio Fernandes; Trevelin, Leonardo Carreira; Paz, Giselle Souza da [UNESP]; Cerqueira, Valiria Duarte (Wiley-Blackwell, 2020)
Histoplasma capsulatum, the fungus causing histoplasmosis, has a strong impact on public health. Histoplasmosis is one of the most prevalent systemic mycoses in the Americas and occurs in several mammalian species. Bats are important in the epidemiological cycle of histoplasmosis because they disseminate the fungus throughout the environment. The aim of the present study was to investigate naturalH. capsulatuminfection in bats located in forested areas, which have undergone anthropogenic perturbations, as well as in the urban areas of the state of Para. Twenty-two species of bats were captured in 18 municipalities of Para; the samples obtained from these animals were subjected to nested PCR for amplification ofH. capsulatumDNA. The HCI/HCII and HCIII/HCIV primers were used, and the final 210-pb fragment was amplified. Of the 100 bats analysed, two were confirmed to be positive forH. capsulatum. Samples amplified by nested PCR were sequenced and found to share identity and have 100% match withH. capsulatumDNA.H. capsulatumwas detected in the area of study: the state of Para has a wide diversity of bat species, and the region under investigation is situated in the north of the state, which suffers the most severe environmental and climatic changes. Therefore, it is essential to elucidate the distribution ofH. capsulatumhosts in this region to facilitate the implementation of effective disease surveillance.
Keywords: Brazilian Amazon; chiroptera; fragmented areas; histoplasmosis; molecular biology